Respostas

A melhor resposta!
  • Usuário do Brainly
2014-08-04T22:44:44-03:00
Sen(a+b)= sena.cosb+sena.cosb

sen(x+x)=sen(2x)
sen(2x)=senx.cosx+senx.cosx
sen(2x)=2senxcosx

sen(2x+x)=sen(3x)
sen(3x)=2senxcosx.cosx + senx.cos2x
sen(3x)=2senxcos²x + senx(cos²x-sen²x)
sen(3x)=2senxcos²x+senxcos²x -sen³x
sen(3x)=3senxcos²x -sen³x

cos²x=1-sen²x
cos²x=1-(-1)²
cos²x=0
cosx=0

sen(3x)=3senxcos²x -sen³x
sen(3x)=-sen³x
sen(3x)=-(-1)³
sen(3x)=1 (c)
1 5 1
2014-08-04T22:45:45-03:00
Fiz a resposta fácil! Está com o anexo!